Assessing yellow stem borer (Scirpophaga incertulas) incidence patterns in paddy (Oryza sativa) cultivation:Implications for climate change adaptation strategies - BALAJI, B N; VIJAYKUMAR, L (The Indian Journal of Agricultural Sciences, 2025)
Rising global food demand and the challenges posed by climate change necessitate sustainable agricultural practices, particularly in staple crop production like rice. The study was carried out during 2022–2023 at College of Agriculture, V C Farm, Mandya, Karnataka to investigate the incidence patterns of the yellow stem borer [Scirpophaga incertulas (Walker)], a significant threat to paddy (Oryza sativa L.) crops, in the context of climate change. The rice variety Jaya was taken for the study. Correlation analyses between meteorological variables and yellow stem borer infestation were performed to understand climate-driven impacts on pest dynamics. Results revealed varying infestation levels across transplanting dates, with early transplanting showing lower infestation rates. The peak pest incidence was recorded on the 15th of October transplanted crop (14.94%), then 1st of October (13.24%) and 15th of March (11.51%). The lowest incidence was observed in 15th January (0.37%) transplanted crop, followed by 1st January and 1st February transplanted crops. Meteorological factors such as minimum temperature and afternoon relative humidity showed a significant positive correlation and morning relative humidity had a significant negative correlation with dead heart. Meanwhile, maximum and minimum temperatures and rainy days recorded a significant negative correlation with white ears. These findings highlighted the critical need for adaptive agricultural strategies that respond to climate variability. Moving forward, strategies such as developing climate-resilient crop varieties and innovative pest management approaches are essential for sustaining rice production and global food security amidst evolving climatic conditions.